2021
DOI: 10.21608/edj.2020.51897.1378
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preheating Cycles on Microshear Bond Strength of Nanohybrid Resin Composite Luted to CAD/CAM Ceramic

Abstract: Objective: This study aimed to investigate the microshear bond strength of adhesive resin cement to Leucite-reinforced CAD/CAM ceramic and compare it with that of prewarmed nanohybrid resin composite. Materials and methods: Sixty Empress CAD ceramic plates were prepared. Each ceramic plate received five Tygon tube micro-cylinders filled with bonding agents creating 5 resinous micro-cylinders on each ceramic plate. In the first group (GpA), they were filled with resin cement, nanohybrid resin composite as a bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Grandio Blocks was reported to have higher absorption coefficient, with higher light penetration before being absorbed, which facilitates the entire photo-polymerization of the photo-polymerized composite [35]. It has been suggested that the use of photo-polymerized composites to bond CAD/CAM materials could be an alternative to the dual-cured resin cements [24,[43][44][45]. By increasing the thickness of luting materials, the chance of incorporation of voids within the cured cement layer is expected to be high [46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Grandio Blocks was reported to have higher absorption coefficient, with higher light penetration before being absorbed, which facilitates the entire photo-polymerization of the photo-polymerized composite [35]. It has been suggested that the use of photo-polymerized composites to bond CAD/CAM materials could be an alternative to the dual-cured resin cements [24,[43][44][45]. By increasing the thickness of luting materials, the chance of incorporation of voids within the cured cement layer is expected to be high [46].…”
Section: Discussionmentioning
confidence: 99%
“…The microhardness and the degree of conversion also showed controversial results, which depended on the resin composite material [21][22][23]. This was shown to be dependent on the number of the pre-heating cycles [24] and the original viscosities of the photo-polymerized composites [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation